Assessment of Noroviruses in selected ulam from local market in Malaysia - Tuan Chilek, Tuan Zainazor; Afsah Hejri, Leili; Mohd Sahroni, Noor Hidayah; Mat Radzi, Noor Eliza; Mohamed Dasuki, Naziehah; Tang, John Yew Huat; Ahmad, Noorlis; Nillian, Elexson; Chai, Lay Ching; Mohd Ghazali, Farinazleen; Cheah, Yoke Kqueen; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Presence of Norovirus in food can cause viral gasteroenteritis. Recently, lots of reports relating to Norovirus in food have been published. Special attention must be paid to the raw foods as they are not subjected to further heat treatment. In this study, pegaga, kesum, tauge and ulam raja (popular salad vegetables in Malaysia) were investigated for Norovirus. A total of 32 samples from each type of salad vegetables were purchased from local market and analyzed using One-step RT-PCR (Reverse Transcriptase-Polymerase Chain Reaction) for both genogroups namely Norovirus Genogroup I and Genogroup II. Results showed that tauge had the highest contamination with Norovirus Genogroup I (15.6%) comparing to pegaga (9.4%), kesum (12.5%) and ulam raja (0%). Samples were free from Norovirus Genogroup II. The study showed that raw vegetables are high-risk foods and can be contaminated with Norovirus.